Physics for You : New National Curriculum edition for GCSE - Johnson, Keith, 1938- (Cheltenham : Stanley Thornes, 1996)
To accommodate the latest National Curriculum requirements this physics textbook has new pages and extra questions added. The book contains a character called Professor Messer who is always making mistakes and students are invited to put him right.
Previous ed.: 1991.
Includes index.
Keywords: Physics; Physics -- Problems, exercises, etc; Popular Science and Mathematics